Several identities in statistical mechanics - M. D. Hirschhorn (International Journal of Mathematics and Mathematical Sciences)
In an earlier paper concerning a solvable Inodel in statistical mechanics, Miwa and Jimbo state a theta-function identity which they have checked to the 200th power, but of which they do not have a proof. The main objective of this note is to provide such a proof.